Quick hits for teaching with digital humanities : successful strategies from award-winning teachers - Morrone, Michael (Quick hits, 2020)
"Quick Hits for Teaching Digital Humanities is an edited collection of 24 articles that aims to introduce faculty, administrators, and staff to ways in which digital techniques from the arts, humanities, and social sciences can be incorporated in the classroom. These techniques can enhance learning and professional development experiences for undergraduate and graduate students and faculty alike. This essential handbook illustrates the breadth of digital humanities across the disciplines with rich examples that bring best practices to life. Anyone who teaches at an institution of higher learning will find entry into new digital paradigms. As the authors share simple and complex ways to introduce digital humanities into the classroom, they expand understandings of what constitutes these current technologies for learning"--